CLINICAL CASE OF PLACENTA ACCRETA - Шибельгут, Нонна Марковна; Батина, Наталья Анатольевна; Мозес, Вадим Гельевич; Рудаева, Елена Владимировна; Елгина, Светлана Ивановна; Мозес, Кира Борисовна (Mother and Baby in Kuzbass, 2025)
Placenta accreta spectrum (PAS) is one of the most dangerous conditions during pregnancy and a pressing issue in obstetrics worldwide. Caesarean section and hysterectomy after delivery with placenta in situ are among the most widely accepted treatment methods. Recently, the practice of inserting inflatable balloons into the pelvic arteries, usually into the anterior internal iliac arteries, as well as installing a balloon into the abdominal aorta has become popular. The article presents a clinical case of placenta accreta into a scar after a cesarean section.
Keywords: pregnancy; placenta; placenta accrete; placenta previa; ultrasound diagnostics